Analisis Kualitas Layanan Terhadap Kepuasan Nasabah Pada Bank Rakyat Indonesia Unit Tatelu Minahasa Utara - Nevrinski Mangaweng; Christien Karambut; Rolyke Tulangow (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2023)
In the current era of digitalization, competition in the business world is getting tougher. Companies must strive to learn and understand the needs and desires of customers. However, customers prioritize quality service, therefore the quality of service is very important in attracting customers' desire to be able to use the products offered by the bank either from deposits or loans. Therefore, the authors want to know more about whether the quality of services provided by the BRI Unit Tatelu bank has been able to meet the wishes and expectations of customers while also wanting to measure the level of service quality provided so as to be able to provide maximum satisfaction to its customers. The purposes of this study are: To determine the effect of service quality on customer satisfaction at the BRI Unit Tatelu bank. This type of research is quantitative research, descriptive research method that describes the phenomenon or problem that is happening in an object of research. This study took a sample from a population by using a questionnaire. The population taken is customers who are still active for transacting at BRI Unit Tatelu with an unknown population, the sample is determined according to Malhotra 2006 by multiplying the number of items by four or five and for the sample obtained 84 people as respondents using a data collection technique, namely convenience sampling. The analysis used is correlation analysis and the results of research analysis of the influence of service quality variables on customer satisfaction.